The performance during four stationary knife attacks: Implications for tactical training - Kantor, Michael; Lewinski, William J.; Reiner, Susannah; Pettitt, Robert (Forensic science international, 2022)
With over 72,000 offenses between 2010 and 2020 in the USA, knives were the third most commonly used weapon in all violent crimes between behind personal weapons and handguns. Examine the performance of different stab (Thrust and overhead) and slash (Figure 8 and Reverse) knife motions to determine how long it takes to execute each motion. In addition, examine the variability in executing each motion to inform future self-defense strategies. Twenty subjects (Females, n = 4; Males, n = 16; Height: 179.96 ± 8.66 cm; Weight: 94.99 ± 22.37 kg; Age: 36.95 ± 10.63 years) who were all active-duty law enforcement officers (LEOs) with 13.52 ± 11.23 years of LEO experience were recruited to participate in the study. Each subject completed two trials of the knife motions while wearing wearable motion sensors (ADPM) and recorded with a high-speed camera (GoPro) while using a training knife (Cold Steel). The time to complete the motions were: Thrust, 0.61 ± 0.15 s; Overhead, 0.68 ± 0.14 s; Figure 8, 1.07 ± 0.21 s; and Reverse, 0.62 ± 0.11 s. The Figure 8 motion was significantly slower than the other three motions: F (3, 57) = 101.19, p < 0.001, ηp2 = 0.84. The reliability analysis reported trivial variability and a high level of agreement: Thrust, ICCα = 0.701, SEM = 0.09 s, CV% = 15.02; Overhead, ICCα = 0.878, SEM = 0.05 s, CV% = 6.93; Figure 8, ICCα = 0.906, SEM = 0.07 s, CV% = 6.25, Reverse, ICCα = 0.420, SEM = 0.10 s, CV% = 17.31. Most LEOs or civilians within striking distance of someone with a knife may not be able to avoid contact from the knife attacks based on the speed knife attacks could occur. The reference data provides pertinent information to update evidence-based training approaches to knife attack preparation and defense. •Knife attacks occurred between 0.61 and 1.07 s.•Close quarters knife attacks can occur faster than typical response time.•Untrained attackers can execute attacks with consistent and fast speeds.•Fastest attack was a thrust stab attack.•Slowest attack was a figure 8 slash attack.